Impact of expectant mother's knowledge level about fetal anomaly scan on their state anxiety prior to antenatal ultrasound screening - SAKALLI KANİ, AYŞE; ESİM BÜYÜKBAYRAK, ESRA; YANARTAŞ, ÖMER; YAVUZER KUZU, ÖZLEM; TOPÇUOĞLU, VOLKAN (TAYLOR & FRANCIS LTD, 2022)
Objective: We aimed to investigate the role of expectant mothers' background antenatal ultrasound knowledge on their state anxiety when they apply for the ultrasound examination. Materials and methods: A cross-sectional study was conducted in perinatology outpatient clinic of a university hospital. Expectant mothers who applied for the first trimester ultrasound scan and second trimester anomaly scan were recruited to the study. A self-report form was applied to participants to assess the sociodemographic characteristics, obstetric history, knowledge and attitudes toward antenatal ultrasound. Expectant mothers' state anxiety prior to ultrasound scan was measured with the state sub-scale of State-Trait Anxiety Inventory. Results: A total of 500 expectant mothers (220 in the first trimester and 280 in the second trimester) were included to the study. We found a negative correlation between the participants' age and state anxiety level (r = -0.118, p < .01). Also, participants' education level had a significant effect on their state anxiety level (F (2, 497)=5.91, p < .01). Participant's age significantly predicted lower state anxiety level (beta = -0.10, t = -2.09, p < .05). We did not find any significant relationship between the mean knowledge level of mothers and state anxiety levels of mothers (r = -0.07, p > .05). Conclusion: Age was the only affecting factor on anxiety levels before ultrasound scan in pregnant participants. There was no significant effect of background knowledge on state anxiety.
Keywords: Anxiety; knowledge; pregnancy; ultrasound